2014
DOI: 10.1519/jsc.0000000000000342
|View full text |Cite
|
Sign up to set email alerts
|

Work Distribution Influences Session Ratings of Perceived Exertion Response During Resistance Exercise Matched for Total Volume

Abstract: Session ratings of perceived exertion (SRPE) are sensitive to changes in total work volume and work rate during resistance training. This study examined the influence of work distribution (varied load, set, and repetitions [reps]) on SRPE in 2 resistance exercise trials matched for total work volume (sets × reps × percentage of 1 repetition maximum [% 1RM]) and work rate (total work volume/time). Participants completed a low load/high rep (LLHR) trial (2 sets × 12 reps × 3-minute recovery at ∼60% 1RM) and a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 27 publications
0
15
0
1
Order By: Relevance
“…Due to the impracticability of using these methods during each training session, researchers have sought easier methods to monitor resistance training. In recent years, perceived exertion scales have been successfully used to regulate resistance exercise intensities (10), monitor the progression of fatigue during workouts (16), estimate changes in the movement velocity or power within a singular set (23), and select the initial training load (17). Robertson et al developed prediction models, which use OMNI-Resistance This is a non-final version of an article published in final form in (provide complete journal citation)…”
Section: Introductionmentioning
confidence: 99%
“…Due to the impracticability of using these methods during each training session, researchers have sought easier methods to monitor resistance training. In recent years, perceived exertion scales have been successfully used to regulate resistance exercise intensities (10), monitor the progression of fatigue during workouts (16), estimate changes in the movement velocity or power within a singular set (23), and select the initial training load (17). Robertson et al developed prediction models, which use OMNI-Resistance This is a non-final version of an article published in final form in (provide complete journal citation)…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, while the current work allows examination of these factors within MCI, future work should incorporate comparison samples of healthy older adults, individuals with Alzheimer disease, and sedentary individuals with MCI. Finally, while our analyses accounted for RPE during the exercise intervention, which is associated with resistance load, 34 we did not control for resistance load itself (eg, percentage of 1-repetition maximum); this may be relevant for our results, as IGF-1 may be more strongly influenced by resistance versus aerobic exercise. 35-36 The role of brain-derived neurotrophic factor must also be considered in future studies, as aerobic exercise increases peripheral brain-derived neurotrophic factor, 37 potentially influencing cognitive change.…”
Section: Discussionmentioning
confidence: 99%
“…The rating of perceived exertion (RPE) scale has been found to be a reliable measure of not only training session intensity, but also specific exercise intensity within a session [234][235]. Although most studies have found RPE an accurate measure of fatigue during strength training, some have found it not to be [236][237][238][239].…”
Section: Rating Of Perceived Exertionmentioning
confidence: 99%